The science of imaging : an introduction - Saxby, Graham (Boca Raton, FL : CRC Press, 2011)
'Edited and expanded to keep pace with the digital revolution, this highly popular and critically acclaimed work continues to provide students with a comprehensive exploration of imaging science. Brilliantly written and extensively illustrated, it covers fundamental laws of physics as well as the cutting-edge techniques that are defining the current direction of the field. It adds a new section on astronomical imaging, as well as major revisions in the areas of digital imaging and modern technology. All references have been updated and now include a significant number of URLs leading to both teaching materials and expanded information. A fundamental introduction to the subject, this volume takes readers on a grand tour of imaging. Starting with the fundamentals of light and basic cameras, the author journeys through television and holography to advanced scientific and medical imaging. Topics such as digital recording of images, the photographic process, and film development are dealt with in an informative and entertaining manner. The book keeps mathematics to a minimum and offers copious examples.'--
Includes bibliographical references and index.
Keywords: Images, Photographic; Photography -- Processing; Image processing; Photography -- Digital techniques